2017
DOI: 10.1002/chem.201605157
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Catalytic Activities of A Nickel(II) Monoamido‐Tetradentate Complex: Evidence For NiIII–Oxo and NiIV–Oxo Species

Abstract: A new mononuclear nickel(II) complex, [Ni (dpaq)Cl] (1), containing a tetradentate monoamido ligand, dpaq (dpaq=2-[bis(pyridin-2-ylmethyl)amino]-N-(quinolin-8-yl)acetamide), has been synthesized and characterized by IR spectroscopy, elemental analysis, and UV/Vis spectroscopy. The structure of the nickel complex has been determined by X-ray crystallography. This nonheme Ni complex 1 catalyzed the epoxidation reaction of a wide range of olefins with meta-chloroperoxybenzoic acid (m-CPBA) under mild conditions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 156 publications
(90 reference statements)
3
20
0
Order By: Relevance
“…The Hammett analysis gave a good linear relationship, with a ρ value of −0.45, which indicated electrophilic character of the reactive oxidant. This value is somewhat lower than those reported for the epoxidation of styrene with [Ni(cyclam)](NO 3 ) 2 ( ρ =−0.82), [Ni(bisamidate)] ( ρ =−0.86), [Ni II (dpaq)Cl] (dpaq=2‐(bis(pyridin‐2‐ylmethyl)amino)‐ N ‐(quinolin‐8‐yl)acetamide) ( ρ =−0.72) and [Ni(Tp CF3Me )( κ 2 ‐ m CPBA)] (Tp CF3Me =hydrotris(3‐ trifluoromethyl‐5‐methylpyrazolyl)borate) ( ρ =−1.35) …”
Section: Resultsmentioning
confidence: 60%
“…The Hammett analysis gave a good linear relationship, with a ρ value of −0.45, which indicated electrophilic character of the reactive oxidant. This value is somewhat lower than those reported for the epoxidation of styrene with [Ni(cyclam)](NO 3 ) 2 ( ρ =−0.82), [Ni(bisamidate)] ( ρ =−0.86), [Ni II (dpaq)Cl] (dpaq=2‐(bis(pyridin‐2‐ylmethyl)amino)‐ N ‐(quinolin‐8‐yl)acetamide) ( ρ =−0.72) and [Ni(Tp CF3Me )( κ 2 ‐ m CPBA)] (Tp CF3Me =hydrotris(3‐ trifluoromethyl‐5‐methylpyrazolyl)borate) ( ρ =−1.35) …”
Section: Resultsmentioning
confidence: 60%
“…We found that 1 epoxidized them in moderate yields (47–51 %). Previously reported non‐heme nickel complexes and porphyrin nickel complexes typically show low catalytic activity towards terminal olefins [12c,j] …”
Section: Resultsmentioning
confidence: 99%
“…The selectivity showed a gradual decrease with increasing chain length. No nickel‐based catalysts are currently known that effect catalytic epoxidation of terminal olefins with such high efficiency and selectivity [12c,j] …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations